The egg clutch and tadpole of Rhinella merianae (Gallardo, 1965) (Anura: Bufonidae) from Central Amazonia, Brazil - Silva, Maria Isabel Da; Schiesari, Luis Cesar; Menin, Marcelo (Zootaxa, 2017)
The Rhinella granulosa group consists of 13 described species with distribution from South America to Panama (Narvaes & Rodrigues 2009; Sanabria et al. 2010; Pereyra et al. 2016). Species belonging to this monophyletic group are characterized by their small to medium body size, ossified skull, small parotoid gland, keratinized cephalic crests and body covered by granules and spicules (Narvaes & Rodrigues 2009; Pereyra et al. 2016). These toads present explosive or prolonged breeding in temporary ponds of open areas (Borteiro et al. 2006; Mercês et al. 2009; Narvaes & Rodrigues 2009; Blotto et al. 2014), where eggs are laid in two long, uniseriate and gelatinous strings (Lima et al. 2012; Blotto et al. 2014; Pereyra et al. 2015). In general, tadpoles of these species are small, round and darkly colored (Blotto et al. 2014). Currently, only seven species have had their tadpoles formally described: Rhinella azarai (Gallardo 1965), Rhinella dorbignyi (Duméril & Bibron 1841), Rhinella fernandezae (Gallardo 1957), Rhinella granulosa (Spix 1824), Rhinella humboldti (Gallardo 1965), Rhinella mirandaribeiroi (Gallardo 1965), and Rhinella pygmaea (Myers & Carvalho 1952) (Fernández 1927; Kenny 1969; Carvalho-e-Silva & Carvalho-e-Silva 1994; Borteiro et al. 2006; Lynch 2006; Mercês et al. 2009; Blotto et al. 2014; Schulze et al. 2015). Pereyra et al. (2016) discussed the taxonomic identity of tadpoles described by Lavilla et al. (2000) as Rhinella major (Müller & Hellmich 1936), and following their concern we do not include these in our comparison. For the Rhinella merianae tadpole, there has been only a brief description (diagrammatic drawings and color patterns in life) in the tadpole identification key from Central Amazonia of Hero (1990) as Bufo granulosus. Therefore, we present in this paper a formal description of the tadpole of R. merianae and additional comments of its clutch size, measurements of eggs and spawning sites.